Identifikasi Kluster Dan Potensi Industri Kecil Dan Kerajinan Rumah Tangga di Wilayah Pulau Sumatera Tahun 1999 dan Tahun 2002 - Nazipawati Nazipawati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2006)
The purposes of this research were to identification where were location of clusters, the distinction of interclusters, leading sub sectors of small and cottage industries and determinant factors of a region was classificationed as industrial district and non industrial district. Used analysis tools were Geographic Information System (GIS), Krugman Regional Divergency Index, Static and Dynamic Location Quotient and discriminant analysis.The results of this research show that location of clusters on 1999 were in regions of Pidie, Aceh Tenggara, Asahan-Deli Serdang, Tanah Datar-Padang Pariaman-Agam, Musi Banyuasin-Palembang, OKU-Lampung Barat-Lampung Tengah-Tanggamus, while on 2002 its were in regions of Pidie, Asahan, Tanah Datar-Limapuluh Koto-Pasaman, Indragiri Hilir, Musi Banyuasin, Lampung Barat-Lampung Tengah-Tanggamus. Based on Krugman’s Index result that the distinction of interclusters showed by existence of distinction of industrial structure on cluster of Tanah Datar-Padang Pariaman-Agam, OKU-Lampung Barat-Lampung Tengah-Tanggamus, Musi Banyuasin-Palembang dan Asahan-Deli Serdang with cluster of Aceh Tenggara on 1999. Almost all clusters, exception cluster of Pidie, had distinction of industrial structure with cluster of Indragiri Hilir on 2002 and at the same year, cluster of Tanah Datar-Padang Pariaman-Agam, Musi Banyuasin, Pidie with cluster of Asahan had a distinction industrial structure. Mainly of sub province in Sumatera Island had leading sub sectors of ISIC 31, ISIC 33, ISIC 36 and ISIC 38. Determinant factors of a region was classificationed as industrial district and non industrial district that identified by discriminant analysis, the result suggests that the best predictors were economic of scale, followed by proportion of foster father, average wages, productivity of labor, and proportion of family worker. Keywords: Cluster, smal and cottage indusry, GIS